Transcriptional profiling of Scedosporium apiospermum enzymatic antioxidant gene battery unravels the involvement of thioredoxin reductases against chemical and phagocytic cells oxidative stress. (8th June 2018) - Staerck, Cindy; Tabiasco, Julie; Godon, Charlotte; Delneste, Yves; Bouchara, Jean-Philippe; Fleury, Maxime J J
Abstract: Scedosporium species rank the second, after Aspergillus fumigatus, among the filamentous fungi colonizing the airways of patients with cystic fibrosis (CF). Development of microorganisms in the respiratory tract depends on their capacity to evade killing by the host immune system, particularly through the oxidative response of macrophages and neutrophils, with the release of reactive oxygen species (ROS) and reactive nitrogen species (RNS). This is particularly true in the airways of CF patients which display an exacerbated inflammatory reaction. To protect themselves, pathogens have developed various enzymatic antioxidant systems implicated in ROS degradation, including superoxide dismutases, catalases, cytochrome C peroxidases, chloroperoxidases and enzymes of the glutathione and thioredoxin systems, or in RNS degradation, that is, flavohemoglobins, nitrate reductases, and nitrite reductases. Here we investigated the transcriptional regulation of the enzymatic antioxidant gene battery in 24-h-old hyphae of Scedosporium apiospermum in response to oxidative stress induced chemically or by exposure to activated phagocytic cells. We showed that 21 out of the 33 genes potentially implicated in the oxidative or nitrosative stress response were overexpressed upon exposure of the fungus to various chemical oxidants, while they were only 13 in co-cultures with macrophages or neutrophils. Among them, genes encoding two thioredoxin reductases and to a lesser extent, a peroxiredoxin and one catalase were found to be overexpressed after chemical oxidative stress as well as in co-cultures. These results suggest that thioredoxin reductases, which are known to be virulence factors in other pathogenic fungi, play a key role in pathogenesis of scedosporiosis, and may be new drug targets.